Overestimation of an Outbreak of Enterobacter cloacae in a Neonatal Intensive Care Unit in Germany, 2015. Issue 6 (June 2019) - Steffen, Gyde; Pietsch, Michael; Kaase, Martin; Gatermann, Sören; Werner, Guido; Fuchs, Stephan; Pfeifer, Yvonne; Schmitt, Wolfgang; Adam, Henning; Eckmanns, Tim; Haller, Sebastian
Abstract : Background: In August 2015, 17 neonates with Enterobacter cloacae (E. cloacae ) colonization were identified in a neonatal intensive care unit (NICU) in Germany. Two developed severe brain abscesses. Despite temporary NICU closure in September, another infant with E. cloacae colonization was detected in October 2015. Methods: We defined potential cases as inpatients treated in the NICU or any pediatric/maternity ward in 2015 with E. cloacae in any specimen before molecular typing. Cases were at first confirmed by arbitrarily-primed-polymerase-chain-reaction and later by XbaI-macrorestriction/pulsed-field gel electrophoresis and next-generation-sequencing. Enhanced barrier precautions and cohorting were implemented for all potential cases and microbiologic screening was extended from NICU to all pediatric/maternity wards. Results: Of 41 potential cases (occurring between 08/04/2015 and 15/11/2015 in 4 wards), the isolates of 23 shared identical arbitrarily-primed-polymerase-chain-reaction patterns; 3 without plausible epidemiologic link. Pulsed-field gel electrophoresis analyses verified only 10 cases (all in the NICU); next-generation-sequencing analysis confirmed these results. In addition 6 cases without isolates available for genotyping were closely linked in place and time. Conclusions: Forty-one suspected patients were cohorted and the NICU was temporarily closed. Further analyses revealed that only 16 cases belonged to the outbreak. Only close interdisciplinary collaboration and highly discriminatory genotyping methods allowed to clearly differentiate between cases and noncases in this E. cloacae outbreak. Abstract : Supplemental Digital Content is available in the text.